The Social Meaning of Language and Dialect - Ernita Daulay (VISION, 2017)
The purpose of human life is to serve, and to show compassion and the will to help others. Language is one of the most important features that separate humanbeings from the animal world. Language is directly connected withthought. Whereas dialect refers to a variation of a language that is characteristic of the users of that language, register refers to a variation of a language that is determined by use a situation or context. Dialects are different ways of saying the same thing; they reflect social structure (e.g., class, gender, and origin). Registers are ways of saying different things; they reflect social processes. Dialects are associated with the linguistic and cultural characteristics of the students who belong to the same broad linguistic group; registers are associated with the characteristics of the language (especially academic language) used in tests. Language as a source of measurement error addresses the fact that bilingual individuals do not typically replicate their capacities across languages